2013
DOI: 10.1021/nn305532k
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization-Dependent Induction of Cellular Survival Pathways by CdSe Quantum Dots in Primary Normal Human Bronchial Epithelial Cells

Abstract: Quantum dots (QDs) are semiconductor nanocrystals exhibiting unique optical properties that can be exploited for many practical applications ranging from photovoltaics to biomedical imaging and drug delivery. A significant number of studies have alluded to the cytotoxic potential of these materials, implicating Cd-leaching as the causal factor. Here, we investigated the role of heavy metals in biological responses and the potential of CdSe-induced genotoxicity. Our results indicate that, while negatively charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 69 publications
2
36
0
Order By: Relevance
“…Negatively charged QDs with MPA (methoxy propyl acetate) capping ligands showed to be relatively noncytotoxic compared to positively charged, cystamine capped, QDs. In contrast, genetical analysis revealed that MPA-QDs induced a high number of DNA-strand breaks 498 due to the upregulation of metallothioneins, which bind the Cd ions that leached from the core and thus reduce the ability for DNA repair. ROI can also induce nucleobase damage of DNA, which is attributed to the abstraction of hydrogen atoms from nucelobases and ribosyl groups.…”
Section: In Vitro Investigationsmentioning
confidence: 92%
“…Negatively charged QDs with MPA (methoxy propyl acetate) capping ligands showed to be relatively noncytotoxic compared to positively charged, cystamine capped, QDs. In contrast, genetical analysis revealed that MPA-QDs induced a high number of DNA-strand breaks 498 due to the upregulation of metallothioneins, which bind the Cd ions that leached from the core and thus reduce the ability for DNA repair. ROI can also induce nucleobase damage of DNA, which is attributed to the abstraction of hydrogen atoms from nucelobases and ribosyl groups.…”
Section: In Vitro Investigationsmentioning
confidence: 92%
“…[59] Specifically regarding QDs, studies have until now only reported that there is a lack of ROS induction by MPA-coated QDs. [34,35] Apart from ROS levels, we looked further into the impact of QD exposure on lysosomal health and autophagy. As a first step we evaluated the influence of QDs on the number and size of lysosomes.…”
Section: Mpa Coated Qdsmentioning
confidence: 99%
“…Analysis of the DNA “comet” tail and nucleoid shape as well as the migration pattern allows for relative assessment of DNA damage. Our previous studies have implemented the comet assay for monitoring the genotoxic effects of cadmium selenide nanoparticles on normal human bronchial epithelial (NHBE) cells7.…”
mentioning
confidence: 99%